P259 Implementation of an expanded hepatology service to improve outcomes in patients with liver cirrhosis. (19th June 2022) - Ahmad, Adeel; Al-Masry, Zainab Abudan; Prabhu, Anil; Gupta, Prakash
Abstract : Introduction: We demonstrate how the introduction of an extended hepatology service has improved our trust's outcomes with regards to variceal bleeding and all-cause mortality in patients with liver cirrhosis. Methods: Spanning a 365-day period over 2017-18, NHS England's Get It Right First Time (GIRFT) initiative audited our trust's outcomes in relation to variceal-bleeding and outcomes for patients with alcohol-related cirrhosis. In response to this, our trust introduced a range of hepatology-specific services including an expanded consultant body, specialist nurses, a liver transplant clinic, dedicated variceal surveillance lists, a day-case paracentesis service and the introduction of streamlined GP referral pathways. We re-audited our outcomes for the calendar year 2019, following implementation of these measures, through interrogation of our trust's coding data and retrospective case note review. Results: GIRFT's initial data outlined that 38.6% of our trust's variceal banding procedures were being performed as an emergency (national average 28.5%), our elective-banding rate was 38.5% (49.5%) and the mortality rate within 30 days of variceal bleeding was 37.5% (13.3%). Our 2019 data demonstrated that the rate of emergency variceal banding dropped to 31.3% and the 30-day mortality rate dropped drastically to 9.5%. Our elective banding rate remained largely the same at 36.4%. With regards to alcohol-related cirrhosis, GIRFT reported that our inpatients' average length of admission was 12.3 days (national average 12.0 days), the re-admission rate was 18.8% (25.6%) and the average all-cause mortality within 30-days of admission was 19.8% (16.0%). Our 2019 data showed a reduction in mortality to 16.7% and a reduction in re-admission rates to 11.1%. The average length of admission, however, increased to 22.9 days. Conclusions: Our data highlights the importance of ongoing development of dedicated hepatology services within district general hospitals. Our trust's mortality figures, most strikingly those relating to variceal bleeding, have drastically improved and this likely represents earlier identification and management of high-risk patients through the newly introduced pathways outlined above. The number of emergency banding procedures we are performing has reduced, likely reflecting an improved adherence to guidelines and appropriate initiation of primary prophylaxis as a result of dedicated variceal surveillance endoscopy lists, and the re-admission rates for those with alcohol-related cirrhosis has reduced, likely as a result of the expansion of our outpatient and day-case services. Our trust's approach can provide a template for similar-sized hospitals who may wish to develop and expand a dedicated hepatology service.